Facies analysis, stratigraphy and marine vertebrate assemblage of the lower Miocene Chilcatay Formation at Ullujaya (Pisco basin, Peru). Issue 2 (13th November 2018) - Di Celma, C.; Malinverno, E.; Collareta, A.; Bosio, G.; Gariboldi, K.; Lambert, O.; Landini, W.; Pierantoni, P.P.; Gioncada, A.; Villa, I.M.; Coletti, G.; de Muizon, C.; et al.
ABSTRACT: This paper is the first integrated account of the sedimentology, stratigraphy, and vertebrate paleontology for the marine strata of the Chilcatay Formation exposed at Ullujaya, Pisco basin (southern Peru). An allostratigraphic framework for the investigated strata was established using geological mapping (1:4000 scale) and conventional sedimentary facies analysis and resulted in recognition of two unconformity-bounded allomembers (designated Ct1 and Ct2 in ascending order). The chronostratigraphic framework is well constrained by integration of micropaleontological data and isotope geochronology and indicates deposition during the early Miocene. The marine vertebrate fossil assemblage is largely dominated by cetaceans (odontocetes), whereas isolated teeth and spines indicate a well-diversified elasmobranch assemblage. Our field surveys, conducted to evaluate the paleontological sensitivity of the investigated strata, indicate that vertebrate remains only came from a rather restricted stratigraphic interval of the Ct1 allomember and reveal the high potential for these sediments to yield abundant and scientifically significant fossil assemblages.